The nature and value of terroir products. (10th April 2017) - Charters, Stephen; Spielmann, Nathalie; Babin, Barry J.
Abstract : Purpose: The aim of this paper is to consider place as a value proposition, in the context of Resource-Advantage Theory, by analysing the concept of terroir, including its antecedents and consequences. Design/methodology/approach: The authors conceptually analyse the role of place in marketing by contrasting terroir to three other approaches: "in the style of […]"; "made in […]" and Protected Designations of Origin. They explore the impact of terroir on a range of products, offering a series of terroir value propositions. Findings: Versus other place links, terroir offers a more specific Resource-Advantage, operating at environmental, philosophical and commercial levels. It offers a unique form of value to both consumers (e.g. identity, authenticity, cultural rootedness) and producers (e.g. irreproducibility, potential legal protection). Research limitations/implications: Propositions address the antecedents and consequences of the terroir designation, the impact of consumer engagement, perceived authenticity and the added value offered to other regional goods. Additionally, how terroir may form a barrier to market entry, the relationship it has with the territorial brand, whether it offers greater product longevity and how it can be used as leverage for other related place-based brands and tourism are examined. Originality/value: This is the first paper to address terroir as a marketing concept and to situate it within other forms of place marketing. It provides a definition, outlines the ways in which terroir creates value and provides a research agenda for future engagement with the concept.